A STUDY ON BIOCHEMICAL PROFILES OF HYDATID CYST FLUIDS FROM RUMINANTS AND HUMANS IN PUNJAB, PAKISTAN - A. A. Latif; M. Mansha; A. Tanveer3 M. S. Rana; S. Fatima (Journal of Animal and Plant Sciences, 2020)
Echinococcus granulosus, a cestode parasite dwells in small intestine of canids and has intermediate hosts such as livestock and humans. Its infection in intermediate hosts results in hydatidosis. The objective of the study was to determine and analyse the biochemical profile manifested by hydatid cyst fluid (HCF) of various ruminants and humans. The fluid was aspirated from fertile and sterile cysts of infected sheep, goat, camel, buffalo, humans and subsequently subjected to biochemical analysis by Randox and Roche kits. The results revealed that in fertile isolates maximum values (mg/dl) of glucose (100.91±6.63), cholesterol (201.21±1.26), triglyceride (192.4±1.83), potassium (119.85±0.49) were recorded in sheep; calcium (10.18±0.24), chloride (107.51±0.37), urea (67.58±0.44) in cattle; protein (g/l) (111.3±5.32), copper (41.24±1.38), urea (73.08±3.68) in camel, Uric acid (13.01±0.36), creatinine (0.20±0.01), magnesium (9.2±0.24) and sodium (122.3±0.64) in human. In sterile isolates highest values of protein (118.39±8.78), magnesium (7.75±0.35) were observed in sheep; calcium (10.2±0.26), potassium (7.83±0.36), sodium (197.23±0.73) in cattle; calcium (7.91±0.23), triglyceride (155.01±8.76), creatinine (0.03±0.01), sodium (19.05±1.22) in buffalo; uric acid (10.69±0.25), glucose (118.97±0.31), urea (372.93±8.92), cholesterol (201.73±2.11), triglyceride (183.39±1.93) in camel and creatinine (0.10±0.01) in human. Hence, biochemical profiles from fertile and sterile isolates showed significant differences among ruminants and human isolates and these parameters can be employed as diagnostic approach for identification of infection.
Keywords: Echinococcus granulosus; biochemical; humans; ruminants; fertile and sterile cysts